Outcomes of surgical treatment of patellar instability in children with Down syndrome - Assem Zein; Alaa Zenhom Mahmoud Hassan; Amr Mohamed Soliman; Mohamed Mohamed Azmy Mohamed (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background patellar instability is a relatively frequent musculoskeletal disorder in children with Down syndrome (DS). However, such a condition has seldom been studied in the literature, even less its surgical treatment. Different techniques have been offered for this condition; the evidence for surgical options is scarce and primarily based on case reports or case series with few patients and heterogeneous techniques. Given this background, we aimed to evaluate the outcomes of a uniform kind of surgical procedure for such a condition that combined lateral soft tissue release, medial patellofemoral ligament (MPFL) reconstruction (using a partial-thickness quadriceps tendon autograft), the Roux-Goldthwait procedure, and V-Y quadricepsplasty (if needed). Materials and methods This retrospective study involved 11 skeletally immature patients (12 knees; 9 males and 2 females), 5.5 to 14.1 years of age, with DS who had patellofemoral instability (PFI) and were managed by this technique between October 2018 and March 2020. Preoperative radiography, CT scan, and MRI were performed to evaluate the physis status, lower limb alignment, patellar height, trochlear morphology, and any associated knee pathology. A functional knee assessment was done by using the Kujala score and the modified Lysholm score. Results The mean time of follow-up (± SD) was 47.7 ± 5.8 months (range: 39–56). Pre-operatively, the Kujala score (± SD) was 52.6 ± 14.3 (range: (31–74), and at final follow-up, it was 92.2 ± 4.4 (range: (88–98), showing a significant improvement (P < 0.001). The preoperative modified Lysholm score (± SD) was 54.3 ± 8.1 (range: 39–62), and at final follow-up it was 92.4 ± 5.3 (range: 82–96), showing a significant improvement (P < 0.001). All patients had a stable patella without a recurrence of instability and regained full ROM. There was no incidence of a patellar fracture or femoral physis injury. Conclusions Our proposed technique of combined soft tissue procedures, including lateral soft tissue release, MPFL reconstruction (using a partial-thickness quadriceps tendon autograft), the Roux-Goldthwait procedure, and V-Y quadricepsplasty, was an effective method for treating patellar instability in children with DS while avoiding physeal injury and patellar fracture. Functional scores and radiological outcomes were improved. Level of evidence IV; retrospective case series.